Physiologically based pharmacokinetic (PBPK) modeling and simulation in drug discovery and development - Abdul Naveed Shaik; Ansar Ali Khan (International Association of Physical Chemists (IAPC), 2019)
Physiologically based pharmacokinetic (PBPK) modeling is a mechanistic or physiology based mathematical modeling technique which integrates the knowledge from both drug-based properties including physiochemical and biopharmaceutical properties and system based or physiological properties to generate a model for predicting the absorption, distribution, metabolism and excretion (ADME) properties of a drug as well as pharmacokinetic behavior of a drug in preclinical species and humans.